The role of intellect (al-'qal) in the discourse of Harun Nasution - Ishak, Mohd. Shuhaimi (Bahagian Pengajian Usuluddin, Akademi Pengajian Islam, Universiti Malaya, 2009)
Harun Nasution is an important name in the reformation of religious thought in Indonesia. His ideal of reformation is modelled along the classical rational thought of Mu'tazilah. He had acquired the profound interest in the theology of the latter while writing his PhD thesis at McGill University, Canada. To him, the Mu'tazilah theology demonstrated the importance of human intellect, that is, Islam is a rational religion, a religion which runs in tandem with reason. The mindset of the society needs to free from dogmatic and legalistic traditions to enable it to realize its potentials and abilities to change from a traditional society to a contemporary society in tandem with the demands of modernization. Harun Nasution believed that Islam is not hosed on narrow and rigid doctrines but in its real essence has a broad and wide horizon and that it allows space for interpretation via allegorical and liberal manner.